The pharmacological and therapeutic effects of carprofen in dogs: Review - Naser, AS; Albadrany , YM; Abdullah, MA (Journal of the Hellenic Veterinary Medical Society, 2026)
The urgent need for new classes of anti-inflammatory drugs to overcome the rapid spread of multidrug-resistant infections in human and veterinary medicine, together with a review of the most important chemical, pharmacological, and pharmacokinetic properties as well as the side effects of carprofen in dogs in previous research, formed the basis of the review in which it was conducted and presented in this article, as previous research confirmed the effectiveness of carprofen in treating pathological conditions related to acute and chronic inflammatory diseases. Relatively speaking, the side effects of this drug were somewhat less than those of other drugs within the same family; therefore, we conclude that it can be used in dogs. Thus, it has a relatively high degree of safety.